006 Secondary amenorrhea related to natalizumab. Issue 6 (27th May 2022) - Obeng, Laurenda; Brown, Heather; Wheately, Trevor; Good, Catriona; Fisniku, Leonora
Abstract : Background: Adverse events are inevitable for many pharmacological interventions, including disease modifying treatment (DMT) in Multiple Sclerosis (MS). Amenorrhoea was reported in less than 2% in phase 3 trials of Natalizumab. Isolated cases have also been reported post marketing.We present a patient who developed secondary amenorrhoea linked to Natalizumab treatment for her relapsing-remitting MS (RRMS). Case: A 36 year old female with highly-active RRMS was started on Natalizumab in June 2014. She developed secondary amenorrhoea by July 2014. Her blood results show low LH, normal FSH and low oestrogen and progesterone and normal thyroid function tests. She remained on Natalizumab for a year and her MS was stable. Due to continuing amenorrhoea Natalizumab was stopped and 3 months later she started menstruating regularly. Her hormonal changes were also normalised. Review of all her imaging from July 2014 – September 2016 revealed no evidence of a pituitary or hypothalamic abnormality or patho- logical enhancement. Patient was subsequently treated with Alemtuzumab and has remained stable. Conclusion: Whereas a simple temporal association between a drug use and a particular event does not necessarily indicate a direct causal relationship, the occurrence of amenorrhoea in our patient linked to the start of Natalizumab and its resolution 3 months post treatment cessation, is too good of a coincidence to be fully dismissed. leonora.fisniku@nhs.net